Adoption of Web-Enabled Student Evaluation of Teaching (WESET) - Raman, Raghu; Nedungadi, Prema (International journal of emerging technologies in learning, 2020)
The “student voice” movement, which advocates for the critical importance of seeking and applying student input into educational decisions such as curriculum development and teaching methods, has been gaining momentum. We examine “student voice” through the vehicle of “Student Evaluation of Teaching (SET)” in the context of higher education. We treat Web-Enabled Student Evaluation of Teaching (WESET) in higher educational institutions as an innovation and apply Diffusion of Innovation theory to study its adoption. We study WESET rates of adoption by analyzing data from 45,934 anonymous student feedbacks of 427 teachers by 1102 students over a period of five years covering both undergraduate and graduate programs at an Indian university. Data from 589 courses in three distinct academic disciplines were collected and analyzed. The adoption rate of the students is primarily attributed to three factors: (a) the guarantee that the system will maintain anonymity, (b) expectation that student feedback will result in positive changes, and (c) ease of use as WESET was integrated into an existing system already used by students. Student evaluations for the same courses significantly improved over each subsequent semester, suggesting that faculty had incorporate student feedback into their curriculum and teaching methods.